1996
DOI: 10.1159/000244289
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Analysis of the Na<sup>+</sup>-K<sup>+</sup> ATPase Activity in Neonatal and Adult Red Blood Cells

Abstract: We studied the role of albuterol in inducing potassium flux mediated by Na+-K+ ATPase in neonatal cells under hyperkalemic conditions. Using rubidium as a tracer element, we determined net transmembrane potassium flux in neonatal and adult red blood cells (RBCs) maintained in a buffer solution containing 10mM KC1. We demonstrated that under these hyperkalemic conditions, albuterol does not increase the net transmembrane potassium flux of the adult RBC. However, neonatal RBCs maintained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These results are in agreement with those of Angelopoulous et al [22] showing a significant diminution in the ouabain-sensitive net K + influx in the neonatal erythrocytes in comparison with the adult erythrocytes. Preliminary experiments carried out with these preparations have shown that the main biochemical characteristics of the Na,K-ATPase (e.g., K m for Na + , K + , and Mg:ATP, optimal pH and temperature, IC 50 for ouabain) are not affected by preeclampsia (data not shown).…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with those of Angelopoulous et al [22] showing a significant diminution in the ouabain-sensitive net K + influx in the neonatal erythrocytes in comparison with the adult erythrocytes. Preliminary experiments carried out with these preparations have shown that the main biochemical characteristics of the Na,K-ATPase (e.g., K m for Na + , K + , and Mg:ATP, optimal pH and temperature, IC 50 for ouabain) are not affected by preeclampsia (data not shown).…”
Section: Discussionsupporting
confidence: 94%
“…The observed salbutamol-induced decrease in serum K + is the result of stimulation of the membrane bound Na + /K + -ATPase by a mechanism that involves the ß 2 -adrenoreceptor [54,69]. The effect of salbutamol on transmembrane potassium flux mediated by stimulation of the Na + /K + -ATPase has been studied in neonatal and adult red blood cells under hyperkalaemic conditions [5]. Salbutamol caused no increase in net transmembrane potassium flux in adult red blood cells, but was associated with a 50% increase of potassium flux in neonatal red blood cells.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The e ect of salbutamol on transmembrane potassium flux has been studied in neonatal red blood cells under hyperkalaemic conditions and resulted in a 50% increase in net transmembrane potassium flux (Angelopoulous 1996). Salbutamol infusion (but not inhalation) for hyperkalaemia has been reported in neonates (Greenough 1992;Dilmen 1992;Avenarius 1996).…”
Section: Description Of the Interventionmentioning
confidence: 99%